PKM Peningkatan Keterampilan Petani Membuat Saluran Pembuangan Air Kotor Rumah Tangga Yang Sehat - Samad, Putri; SM, Alimuddin; CA, Ganggang (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
Farmers in the Samangki Village area, Simbang Sub-district, Maros Regency are the target community for this community service activities. Samangki Village has an area of 43.62 km² and a population of 5,176 people with a population density of 118.66 people/km². Farmers' knowledge of environmental sanitation is still relatively low so it is necessary to provide guidance and guidance in improving the quality of the environment and housing in Samangki village. The purpose of this community service activities is that farmers in Samangki Village can make healthy household sewage drains. In addition, it is also hoped that smallholder families can improve the quality of their housing environment and overall quality of life. The implementation method includes the following stages: (1) Licensing and Site Preparation, (2) Socialization, (3) Counseling, (4) Introducing Materials and Tools, and (5) Program Monitoring and Evaluation. The results of this community service activities are: (a) Improved Farmer Skills: Through intensive training and mentoring, farmers in this area successfully improved their understanding of basic sanitation principles and simple construction techniques for sewerage, (b) Reduced Disease Risk: With the implementation of healthy sewerage, the risk of disease transmission caused by dirty water can be significantly reduced, (c) Improved Quality of Life: Farmer households that have participated in the program experience a marked improvement in quality of life, feeling safe and comfortable with a clean and healthy environment, and (d) Improved Quality of Life: Farmer households that have participated in the program experience a marked improvement in quality of life. This community service activities achieved a number of significant results. Intensive training and mentoring to farmers in the region has brought about tangible positive impacts.